2016
DOI: 10.1111/mono.12239
|View full text |Cite
|
Sign up to set email alerts
|

Iv. Testing for Dosage‐outcome Associations in Early Care and Education

Abstract: Investing in our future: The evidence-base on preschool education. Foundation for Child Development. https://files.eric.ed.gov/fulltext/ED579818.pdf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…Our findings are also different from other dosage studies that find positive effects of a second year of Head Start but that gains in the second year were much smaller than the first (e.g., Xue et al, 2016). These studies compare children who attend Head Start at ages 3 and 4 to children who attend Head Start at age 4 only and do not account for the comparison group’s care environment at age 3.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are also different from other dosage studies that find positive effects of a second year of Head Start but that gains in the second year were much smaller than the first (e.g., Xue et al, 2016). These studies compare children who attend Head Start at ages 3 and 4 to children who attend Head Start at age 4 only and do not account for the comparison group’s care environment at age 3.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of these studies use PS methods that match children who enter Head Start at age 3 and stay through age 4 to children who participate only in age-4 Head Start to address selection bias into dosage. Using the 2006 and 2009 Family and Child Experiences Survey (FACES) data—a nationally representative, cross-sectional observational study of Head Start programs and participants collected regularly by the Office of Head Start—Xue and colleagues (2016) find that children who entered Head Start at age 3 and stay for their age-4 year had modestly higher vocabulary scores relative to children who participated in Head Start at age 4 only, with the gains from the second year being much smaller than the first (ES of second year = 0.10–0.17). Using the same comparison groups in the 2003 FACES data, another PS study found larger effects from 2 years of Head Start relative to 1 year (effect size (ES) = 27–0.80; Wen, Leow, Hahs-Vaughn, Korfmacher, & Marcus, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although exposure to ECE seems to be related to children’s academic outcomes (e.g., Xue et al, 2016), effects on socio-behavioral outcomes are less clear. Some studies have reported positive effects of exposure to high-quality ECE classrooms, namely, for children from low-income backgrounds (Zaslow et al, 2010); however, other studies have found no effects of ECE exposure on children’s social skills and problem behaviors (Xue et al, 2016). Importantly, no previous studies have focused on the role of ECE dosage on the social experiences of children with disabilities.…”
mentioning
confidence: 99%
“…Classroom processes may influence development in different ways, depending on their frequency and duration (Bronfenbrenner & Morris, 2006), which may help explain the low to moderate effect sizes reported for ECE quality. Different approaches to measuring children’s exposure to ECE, or dosage, include hours per day or per week and attendance (Xue et al, 2016; Zaslow et al, 2010). Although exposure to ECE seems to be related to children’s academic outcomes (e.g., Xue et al, 2016), effects on socio-behavioral outcomes are less clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation